1985
DOI: 10.1079/bjn19850139
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the degradability of dietary protein in the sheep rumen by in vivo and in vitro procedures

Abstract: 1. Estimates of degradability of nitrogen in the sheep rumen for a basal hay diet and for soya-bean meal (SBM), groundnut meal (GNM) and fish meal (FM), when given together with the hay, were determined from measurements of (1) duodenal N flow, (2) ammonia kinetics and (3) rumen N disappearance from polyester bags and rumen outflow rate. The ability of various in vitro procedures to predict in vivo N degradability was also examined.2. Four sheep were given a basal hay diet (800 g dry matter (DM) and 19 g N/d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Comparing both methods, Mathers and Miller (1981) and Siddons et al (1985b) found a close agreement and protein degradability ranked in the same order but other reports in the literature have not found such an agreement (Kennedy et ah, 1984). Comparing both methods, Mathers and Miller (1981) and Siddons et al (1985b) found a close agreement and protein degradability ranked in the same order but other reports in the literature have not found such an agreement (Kennedy et ah, 1984).…”
Section: Comparisons Of Estimates Of Degradability With Flow Measuremsupporting
confidence: 61%
“…Comparing both methods, Mathers and Miller (1981) and Siddons et al (1985b) found a close agreement and protein degradability ranked in the same order but other reports in the literature have not found such an agreement (Kennedy et ah, 1984). Comparing both methods, Mathers and Miller (1981) and Siddons et al (1985b) found a close agreement and protein degradability ranked in the same order but other reports in the literature have not found such an agreement (Kennedy et ah, 1984).…”
Section: Comparisons Of Estimates Of Degradability With Flow Measuremsupporting
confidence: 61%
“…Ruminal NH 3 -N concentrations were consistently higher ( P b 0.05) in sheep fed diets containing wormwood within 2 h after feeding, reflecting higher CP digestibility in sheep fed wormwood diets (Chamberlain and Thomas, 1979;Siddons et al, 1985;Kim et al, 2002a). Ruminal total VFA concentrations were generally higher in sheep fed MW and LW than those fed the other diets between 1 and 2 h after feeding.…”
Section: Butyric Acidmentioning
confidence: 93%
“…It is crucial for the efficient use of ingested forage by ruminants that release of energy derived from plant carbohydrates is matched with the liberation of protein degradation products. Often, however, nitrogen availability in the rumen exceeds energy supply leading to reduced microbial production efficiencies, increased deamination of plant proteins and excessive production of rumen ammonia and loss of nitrogen in urine (McRae et al ., 1985; Dewhurst et al ., 1995; Siddons et al ., 1995; Dewhurst et al ., 2000). Determining the underlying causes of poor nitrogen use efficiency in the rumen would help remedy these problems and would contribute to improve the efficiency of livestock production and reduce excessive nitrogen excretion to the environment.…”
Section: Introductionmentioning
confidence: 99%